2011
DOI: 10.1097/ftd.0b013e3182399448
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir, an Influenza Neuraminidase Inhibitor Drug, Does Not Affect the Steady-State Pharmacokinetic Characteristics of Cyclosporine, Mycophenolate, or Tacrolimus in Adult Renal Transplant Patients

Abstract: These data from a single Os dose study suggest that coadministration is not expected to cause adverse symptoms nor alter the steady-state PK of CyA, mycophenolate mofetil, or Tac in stable adult renal transplant patients with mild renal insufficiency. The data enable a multiple-dose study that reflects clinical practice during influenza exposure and assesses the possibility that chronic exposure to Os might result in a different outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…56 Importantly, pharmacokinetic studies have not observed a clinically relevant interaction between oseltamivir and immunosuppressive drugs (tacrolimus, cyclosporine, and mycophe nolate). 57 The use of the intravenous drugs peramivir or zanamivir can be considered in cases of lifethreatening infection or concerns with oral absorption, although, as mentioned, experience with these drugs in SOT recipients is lacking. 50,51 The use of amantadine and rimantadine for treatment of influ enza is no longer recommended due to the high rate of resistance to these drugs (>95%).…”
Section: Treatmentmentioning
confidence: 99%
“…56 Importantly, pharmacokinetic studies have not observed a clinically relevant interaction between oseltamivir and immunosuppressive drugs (tacrolimus, cyclosporine, and mycophe nolate). 57 The use of the intravenous drugs peramivir or zanamivir can be considered in cases of lifethreatening infection or concerns with oral absorption, although, as mentioned, experience with these drugs in SOT recipients is lacking. 50,51 The use of amantadine and rimantadine for treatment of influ enza is no longer recommended due to the high rate of resistance to these drugs (>95%).…”
Section: Treatmentmentioning
confidence: 99%
“…Recently, in a lethal mouse infected with influenza A (H1N1 and H5N1), oseltamivir combined with an mTOR inhibitor (everolimus) was shown to significantly delay death, as well as reduce pulmonary hemorrhage (37). Oseltamivir has little potential for drug interactions, and coadministration is not expected to cause adverse symptoms nor alter the steady-state pharmacokinetics of tacrolimus (the mTOR inhibitor), in stable adult renal transplant patients with mild renal insufficiency (38). Oseltamivir has little potential for drug interactions, and coadministration is not expected to cause adverse symptoms nor alter the steady-state pharmacokinetics of tacrolimus (the mTOR inhibitor), in stable adult renal transplant patients with mild renal insufficiency (38).…”
mentioning
confidence: 99%
“…No interactions with the cytochrome P450 enzymes occur in vitro and oseltamivir does not affect the steady-state pharmacokinetics of commonly used immunosuppressive agents. 55 However, probenecid blocks tubular secretion and doubles the half-life of oseltamivir. Protein binding is less than 10%.…”
Section: Laninamivirmentioning
confidence: 99%